Proyecto de factibilidad para la creación de una empresa de servicios de gestion de tramites para la ciudad de Loja - Medina León, Eunice Salome (2017)
The present investigation was carried out with the objective of determining the feasibility for the creation of a service management services company in the city of Loja. It is important to indicate that in the city of Loja does not have a company that facilitates the procedures that day to day people need to perform. As techniques were the surveys applied to a sample of the 81,743 comprised of 30 to 64 of the city of Loja according to projections of the INEC (2010). The results show the data obtained from the application of interviews and surveys related to demand, supply, product, per capita consumption, among other data that served as a basis for carrying out the necessary studies in the project. The discussion is divided in each study applied in the project starting with the market where 47,370 people were established as effective demand, with an annual per capita use of 9 units. As for the supply generating an unsatisfied demand of 26370 paperwork for the first year. The second study is the technician establishing an installed capacity of 4,680 units, of which 75% will be used for the first year, which indicates a used capacity of 3,510 services of procedures. In the administrative study the legal organization was established, indicating as a corporate name "GESTI TRAMITES" associates, a social object of the Provision of Services of Management of Tramites, with a duration of 10 years the project and an investment of $ 11,205.30 of which the contribution of the partners is 100%, so that each partner will contribute with $ 5,602.65. In addition, the draft constitution is presented, indicating the name of the two partners that make up the Shareholders' Meeting. Structural, functional and positional organization chart of the positions with which the company will start and a manual of functions that delimits the activities to be carried out in each one of these positions. The economic study is made up of the investment plan which shows fixed assets (3,660.79), deferred assets (1,542.22) and current assets (6,002.29), generating a total of $ 11,205.30 in investments. Financing will be internal and by equal shares of the partners. The financial evaluation indicates positive values for which cash flow data are required for the first year is $ 10,676.03 and with positive values in the following years, a NPV of $ 58,481.83 is obtained, a TIR of 98 , 30%, an RBC of 1.25 means that for every dollar invested you get 0.25 cents of profit, the PRC is 1 years, 0 months, 18 days and finally the sensitivity analysis indicates that the project can support a A maximum increase of 16.47% of costs and a decrease of no more than 13.17% of revenues. The conclusions show the feasibility of the project and the importance of its constitution in the market of the province of Loja due to the lack of management services companies.